2020
DOI: 10.1155/2020/3231273
|View full text |Cite
|
Sign up to set email alerts
|

Low UGP2 Expression Is Associated with Tumour Progression and Predicts Poor Prognosis in Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a malignant tumour associated with a high mortality rate and poor prognosis worldwide. Uridine diphosphate-glucose pyrophosphorylase 2 (UGP2), a key enzyme in glycogen biosynthesis, has been reported to be associated with the occurrence and development of various cancer types. However, its diagnostic value and prognostic value in HCC remain unclear. The present study observed that UGP2 expression was significantly downregulated at both the mRNA and protein levels in HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…The study of Wang et al suggested that overexpressed miR-93-5p enhanced the proliferation capacity of HCC by inhibiting the expression of PPARGC1A. A previous study suggested that low UGP2 expression was independently associated with poor prognosis of HCC (Hu et al, 2020). ILVBL is the major 2-OH acyl-CoA lyase involved in the cleavage reaction in the fatty acid α-oxidation of the phytosphingosine degradation pathway (Kitamura et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The study of Wang et al suggested that overexpressed miR-93-5p enhanced the proliferation capacity of HCC by inhibiting the expression of PPARGC1A. A previous study suggested that low UGP2 expression was independently associated with poor prognosis of HCC (Hu et al, 2020). ILVBL is the major 2-OH acyl-CoA lyase involved in the cleavage reaction in the fatty acid α-oxidation of the phytosphingosine degradation pathway (Kitamura et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Of interest for future study are top sensitivity hit UGP2 and resistance hit COPS4 which were the most lowly expressed and highly expressed screen hits in the large chemotherapy treatment‐resistant breast cancer patient tumor cohort. Although not studied in the context of breast cancer, UGP2 expression (both high and low) has been implicated in the progression of other cancers [47,48], and our data suggest a potential uncharacterized role for UGP2 in breast cancer in the context of treatment. COPS4 is part of the multisubunit COP9 that plays roles in DNA repair and cell cycle regulation in part through modulating the activity of E3 ubiquitin ligases [49].…”
Section: Discussionmentioning
confidence: 81%
“…Zeng et al found that UGP2 was identified as a progression marker that promotes the growth and motility of human glioma cells and performs a crucial role in the proliferation of LGG (Zeng et al, 2019). Hu et al found that low UGP2 expression was associated with tumor progression and poor prognosis for HCC (Hu et al, 2020). Nonetheless, studies on the function of UGP2 in tumors are limited, particularly in LGG.…”
Section: Discussionmentioning
confidence: 99%